Blood eosinophil cationic protein and eosinophil-derived neurotoxin are associated with different asthma expression and evolution in adults. Issue 6 (6th October 2021) - Granger, Vanessa; Zerimech, Farid; Arab, Jinan; Siroux, Valerie; de Nadai, Patricia; Tsicopoulos, Anne; Matran, Régis; Akiki, Zeina; Nadif, Rachel
Abstract : Background: Eosinophil-derived neurotoxin (EDN) and eosinophil cationic protein (ECP) are proteins released by activated eosinophils whose role in adult asthma remains unclear. Objective: To study associations between ECP, EDN and various asthma characteristics in adults from the Epidemiological Study on the Genetics and Environment of Asthma (EGEA). Methods: Plasma ECP and EDN levels were measured by ELISA. Cross-sectional analyses were performed in 941 adults (43±16 years old, 39% with asthma) at EGEA2 (2003–2007). Longitudinal analyses investigated the associations between EDN level at EGEA2 and changes in asthma characteristics between EGEA2 and EGEA3 (2011–2013, n=817). We used generalised estimated equations adjusted for age, sex, smoking status and body mass index to take into account familial dependence. Results: At EGEA2, both high ECP and EDN levels were associated with current asthma (adjusted OR (aOR) (95% CI): 1.69 (1.35–2.12) and 2.12 (1.76–2.57)). Among asthmatics, high EDN level was associated with asthma attacks (aOR: 1.50 (1.13–1.99)), wheezing and breathlessness (aOR: 1.38 (1.05–1.80)), use of asthma treatments (aOR: 1.91 (1.37–2.68)) and bronchial hyper-responsiveness (aOR: 2.03 (1.38–2.97)), even after further adjustment on ECP. High ECP level was associated with high neutrophil count and tended to be associated with chronic bronchitis. High EDN level at EGEA2 was associated with persistent asthma (aOR: 1.62 (1.04–2.52)), nocturnal symptoms (aOR from 2.19 to 3.57), worsening wheezing and breathlessness (aOR: 1.97 (1.36–2.85)) and nocturnal shortness of breath (aOR: 1.44 (1.04–1.98)) between EGEA2 and EGEA3. Conclusions: EDN and ECP were associated with different asthma expression in adults. EDN could be a potential biomarker to monitor asthma evolution in adults.